Construction safety risk assessment with introduced control levels - Gunduz, Murat; Laitinen, Heikki (Journal of Civil Engineering and Management, 2018)
It is of great importance to facilitate the risk assessment process in construction projects because risk assessment is a requirement in most legislation and safety standards. A great majority of construction SMEs (Small and Medium Enterprises) are not familiar with risk assessment concepts and methods. In particular, SMEs are very likely to have difficulty finding the qualified personnel or time to carry out a proper risk assessment. The method introduced in this paper has some distinct features. The method introduces a new method of risk assessment, replacing the traditional definition of probabilities with control levels because they are easier to implement and yield more accurate risk scores. The method was practically applied on 22 construction SMEs. From the practical application, it was observed that the method was found to be user friendly and the SMEs found it easy to update their risk strategies during various construction stages in their projects. The proposed risk assessment method introduces a powerful and practical control level strategy which would develop a safer, healthier and more competitive workplace for construction SMEs.